Teenagers in Vortex Emotions: Reveal the Secrets of Aggressive Behavior - Siti Hapsoh (CV. Doki Course and Training, 2025)
Aggressiveness is a form of intentional harm to others, a tendency to behave in a way that can hurt others, either physically or verbally that can destroy property intentionally, which is manifested in very strong counter behavior, such as saying harsh words, bullying, threatening, fighting, injuring, attacking, damaging facilities, stabbing, and even killing. In general, these behaviors often appear at the adolescent stage of development. This systematic review aims to analyze 16 national and international journals on adolescent aggressiveness behavior. The results of this systematic review found that there are factors of aggressive behavior in adolescents, aggressiveness behavior in adolescents is influenced by internal and external factors. These internal factors include: frustration, impaired thinking and intelligence of adolescents, and emotional disorders in adolescents while external factors include family or peer factors, school factors and environmental factors. Aggressive behavior in adolescents can actually be minimized and even reduced, one of which is through positive activities and controlling negative behaviors.